The Practice of Cash Based Waqf In The Indonesian Islamic Banking - Ainul Fatha Isman; Andi Suwandi Putra Suaib (Universitas Islam Negeri Alauddin Makassar, 2022)
Islamic banking is a Islamic financial institution that has obligations on the social dimension by utilizing Islamic social finance institutions is cash waqf. The purpose of this study is to analize the implementation of cash waqf in Indonesia and significance of Islamic banks in managing cash waqf and to provide a model for developing cash waqf by Islamic banks. This research is a qualitative descriptive analysis with an inductive reasoning approach through the process of content analysis and library research. The results of this study indicate Islamic banking has become part its management, but has not optimal. Islamic banks only collect funds, while the management and distribution of them become the responsibility of nazhir. The significance of Islamic banking to manage cash waqf has advantages in terms of professionalism, transparency, accountability, facilities, technology infrastructure, human resources, risk level, extensive network, easy access, and public trust. The research also formulated a cash waqf management model in the form of synergy of Islamic banking with waqf nazhir and customers. The implications of this research are so that Islamic banks regard to management mecanism of cash wqaf and it regulatory aspects to improve the optimization of cash waqf management in Indonesia and provide benefits for Islamic banks and restore the image of Islamic banks to their social functions.